Similarities and differences in European conceptions of human resource management: Toward a polycentric study - CLARK, Timothy Adrian Robert (Institutional Knowledge at Singapore Management University, 2000)
Increasingly managers need to distinguish between those oftheir activities and practices that can be successfully transferred acrossnational boundaries and those that will require modification in view ofdivergences between national settings. This can be determined by initiallyidentifying those features of managing organizations that remain similar acrossnational boundaries and those that are different, and then ascertaining thestrength of the forces for convergence or divergence. This article describes anexploratory attempt to conduct a polycentric (in the terms described below)research study of conceptions of human resource management in seven Europeancountries. It examines whether there is a single, shared conception of HRM thattranscends national boundaries, or whether there are multiple national meaningsreflecting a variety of cultural and institutional contexts that cannot beintegrated into a single truly "international,""transnational," or European model. This research is presented as adistinctive contribution to the debate on the global convergence of management.